The changing pattern of analgesic and anti-inflammatory drug use in cleft lip and palate repair - Santos, Carlos F.; Calvo, Adriana M.; Sakai, Vivien T.; Dionisio, Thiago J. [UNESP]; Lauris, Jose R. P.; Carvalho, Roberta M.; Trindade, Alceu S. (Elsevier B.V., 2006)
Objective. This work aimed at performing a retrospective and comparative investigation of pharmacological therapeutic approach for pain and inflammation control for cleft lip and/or palate repair.Study design. Medical charts from 2000 patients who underwent surgical procedures at the Hospital for Rehabilitation of Craniofacial Anomalies, University of So Paulo (HRAC-USP), Brazil, were assessed to obtain information regarding type of cleft, surgical procedure, and analgesic and anti-inflammatory drugs prescribed. The first 1000 consecutive surgeries performed in 1 992 and 2002 were assessed.Results. Different analgesic and anti-inflammatory agents-nonsteroidal anti-inflammatory drugs (NSAIDS), steroids, and opioids-were given to patients perioperatively and postoperatively. NSAIDS were given to almost all patients (97.03% in 1992 and 99.88% in 2002, P > .05). Steroid administration increased in 2002 (8.66% versus 17.71%, P < .05). Opioids were administered only in 2002 (50.31%, P < .05).Conclusion. NSAIDS, steroids, and opioids were used for pain and inflammation control in cleft lip and palate repair at HRAC-USP. A change in the pattern of analgesic and anti-inflammatory drug use was observed when comparing 1992 and 2002. More potent compounds, such as opioids, were used in 2002 in a significant percentage of all the surgical procedures. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2006;102:e16-e20)